The middle Miocene palynoflora and palaeoenvironments of Eskihisar (Yatağan basin, south‐western Anatolia): a combined LM and SEM investigation. (27th June 2016) - Bouchal, Johannes M.; Zetter, Reinhard; Grímsson, Friđgeir; Denk, Thomas
Abstract : We investigated a palynological section from middle Miocene sediments at Eskihisar (south‐western Anatolia) to establish biogeographic links of the palynoflora and to infer the palaeoenvironment. Four algal palynomorphs, nine spore taxa, eight gymnosperms, three monocots and 67 dicot pollen types were encountered and investigated using the 'single grain method' that combines light microscopy and scanning electron microscopy. Two pollen zones reflect different phases of basin development. Zonal vegetation remained fairly stable across the section and reflects heterogeneous environments including broad‐leaved deciduous forest, subtropical forest and sclerophyllous and semi‐evergreen oak forest. Conifers were accessory elements in the broad‐leaved deciduous forest communities and replaced these at higher elevations. Some herbaceous taxa (Plumbaginaceae) indicate scattered occurrences of sandy and/or rocky soils. Biogeographic affinities are general Northern Hemisphere, North American and East Asian, as also suggested by the macrofossil record. Only two taxa provide potential biogeographic links with the African flora. This suggests that biome shifts of plant taxa between African subtropical/tropical biomes and Anatolian (western Eurasian) temperate forests and shrublands may have been rare in the middle Miocene.